ANALISIS FAKTOR MOTIVASI KERJA KARYAWAN (Studi Kasus pada PT Orela Shipyard) - Liliana Dewi; Michael Christopher Doullos Thorion (Politeknik Ubaya, 2019)
PT Orela Shipyard is a family company running the shipping industry. In the two recent years, the company’s turnover becomes fluctuated, this change is caused by some factors, one of them is the employee work motivation. The purpose of this research is to find out the factors that motivate the employee works of PT Orela Shipyard. The data used are primary data with data collection techniques by using a questionnaire.The sample that is used is 60 employees of PT Orela Shipyard that consist of 30 office employees and 30 shipyard employees with a simple random sampling technique and that are processed by using SmartPLS 3.0 software program. This research uses a first-order construct and second-order construct tests. The results of this research indicate that the variables of work safety, award, achievement, salary, relationship with superiors and work conditions are the factors that motivate the work of the employees at PT Orela Shipyard.